1992
DOI: 10.1177/1046878192233001
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Games for Educational Purposes: A Review of Recent Research

Abstract: This article reviews the literature that compares the instructional effectiveness of games to conventional classroom instruction. Studies dealing with empirical research rather than teachers'judgments are reviewed. Published reviews of research in English dating from 1963 to 1984 were examined and the literature was searched for studies from 1984 to 1991. Of the 67 studies considered over a period of 28 years, 38 show no difference between games and conventional instruction; 22 favor games; 5 favor games, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
330
0
15

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 572 publications
(347 citation statements)
references
References 26 publications
2
330
0
15
Order By: Relevance
“…In our work, the main aspect to check was the learning outcomes. Reviewing previous work, comparing new methods with traditional methods seems to be a common technique (Randel et al, 1992;Rosas et al, 2003;Ebner and Holzinger, 2007;Telner et al, 2010;Yang, 2012;Chen and Tsai, 2012). Following this trend, we compared our proposal with traditional games.…”
Section: New Methods Vs Traditional Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our work, the main aspect to check was the learning outcomes. Reviewing previous work, comparing new methods with traditional methods seems to be a common technique (Randel et al, 1992;Rosas et al, 2003;Ebner and Holzinger, 2007;Telner et al, 2010;Yang, 2012;Chen and Tsai, 2012). Following this trend, we compared our proposal with traditional games.…”
Section: New Methods Vs Traditional Methodsmentioning
confidence: 99%
“…Following this trend, we compared our proposal with traditional games. Randel et al (1992) reviewed the literature that compared the instructional effectiveness of games to conventional classroom instruction. Studies dealing with empirical research rather than teachers' judgments were reviewed.…”
Section: New Methods Vs Traditional Methodsmentioning
confidence: 99%
“…Educational software that uses a "game-like" approach has been shown to have a strong cognitive effect on students learning science-based concepts, akin to problem solving in the cognitive processes that are generated 3,4 . According to Randel et al 3 games foster greater interest from students when compared with traditional forms of instruction.…”
Section: Etop 2009mentioning
confidence: 99%
“…32 Others emphasize the fantasy or imaginative nature of games 33 and the competitive nature of games. 34 Prensky 35 identifies, and claims, that computer games are characterized by six "structural elements" that come together to create the engaging experience he argues is the key to using computer games as effective learning tools. The elements are: rules, conflict (competition, challenge, opposition), goals (objectives), interaction, outcomes (feedback), representation (story).…”
mentioning
confidence: 99%
“…An early review of pre-1991 studies 63 found that serious games (for the most part not computer based)…”
mentioning
confidence: 99%